RANCANG BANGUN APLIKASI PEMESANAN DAN PENJADWALAN PERMAINAN GOLF DI GOMBEL GOLF SEMARANG BERBASIS WEB MOBILE (Information Technology and Telematics, 2015)
Abstract- The booking system is running at Gombel Golf Semarang still use the phone. Booking and scheduling system that is currently running on Gombel Golf Semarang still using Microsoft Excel so reservations are not even seem less effective, both in terms of time, as well as the processing and management of data. In this study, the authors will implement reservation and scheduling applications web-based mobile golf cart at Gombel Golf Semarang. System development method used in this study is a prototype that consists of a collection of needs, build prototyping, evaluation, prototyping, coding systems, test systems, evaluation systems, using the system. System design using OOD which consists of the use case diagrams, activity diagrams, sequence diagrams and class diagrams. Program development using PHP, Java and MySQL. The end result of this research is already successfully made the booking and scheduling applications golf game on android based Gombel Golf Semarang can be used to manage the booking and scheduling golf and allows members to book a golf course in accordance with the desired game Keywords – Booking, Scheduling, Gombel Golf Semarang